Assessing the risks of dietary quercetin supplementation in red-spotted grouper (Epinephelus akaara): effects on growth performance, antioxidant capacity, lipid level, and intestinal microbiome - Hu, Yuan; Li, An; Shao, Xinbin; Zhu, Jie; Cai, Jingbo; Ma, Jianzhong; Lu, Rongmao (Frontiers in Marine Science, 2025)
Quercetin, a naturally occurring plant flavonoid, is used in aquaculture feeds to affect fish health. This study evaluated the effects of dietary quercetin supplementation on the growth performance, antioxidant capacity, lipid levels, and gut microbiota in juvenile Epinephelus akaara. Fish were reared in a controlled recirculating aquaculture system and received dietary quercetin for 8 weeks at five levels: 0, 181, 362, 544, and 725 mg/kg. Growth metrics, physiological and biochemical parameters, antioxidant enzyme activities, and intestinal microbial communities were assessed using standard analytical protocols. Quercetin supplementation at 362–544 mg/kg significantly increased the weight gain rate and the specific growth rate. It elevated the activities of key antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), while reducing malondialdehyde (MDA) levels. Supplementation of quercetin at 181–725 mg/kg lowered the levels of cholesterol (TC) in liver and muscle as well as triglyceride in liver. It also increased gut microbiota diversity and enriched beneficial taxa, such as Cetobacterium, Romboutsia, and Turicibacter, which were positively correlated with physiological resilience. Cetobacterium was correlated significantly negative with cholesterol (r < −0.6, P < 0.01). These findings suggest that quercetin is a promising functional feed additive for improving health and aquaculture performance in red-spotted grouper.